2008
DOI: 10.1038/leu.2008.251
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing survival after relapse from acute lymphoblastic leukemia: a Children's Oncology Group study

Abstract: Despite great progress in curing childhood acute lymphoblastic leukemia (ALL), survival after relapse remains poor. We analyzed survival after relapse among 9585 pediatric patients enrolled on Children's Oncology Group clinical trials between 1988 and 2002. A total of 1961 patients (20.5%) experienced relapse at any site. The primary end point was survival. Patients were subcategorized by the site of relapse and timing of relapse from initial diagnosis. Time to relapse remains the strongest predictor of surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
431
7
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 498 publications
(477 citation statements)
references
References 35 publications
(30 reference statements)
23
431
7
2
Order By: Relevance
“…[68][69][70][71][72][73][74][75][76][77][78] While in the era of genomics the number of papers in the field of leukemia has risen amazingly, it remains difficult to filter out the information, which can be used for improved treatment quality and better prevention of disease recurrence. Certainly one prerequisite is reproducibility of data, and thus, uniform approaches are needed if such techniques shall be used routinely in clinical diagnostics and for risk assessment.…”
Section: Discussionmentioning
confidence: 99%
“…[68][69][70][71][72][73][74][75][76][77][78] While in the era of genomics the number of papers in the field of leukemia has risen amazingly, it remains difficult to filter out the information, which can be used for improved treatment quality and better prevention of disease recurrence. Certainly one prerequisite is reproducibility of data, and thus, uniform approaches are needed if such techniques shall be used routinely in clinical diagnostics and for risk assessment.…”
Section: Discussionmentioning
confidence: 99%
“…In a diagnostic cytogenetics laboratory for hematological malignancies, supplementary tests such as FISH and RT-PCR studies are usually performed as well. Although the five-year survival rate of children with ALL has exceeded 85%, survival after relapse remains poor [41]. Cytogenetic and molecular cytogenetic studies revealed chromosomal abnormalities in only about 80% of ALL [42].…”
Section: Discussion and Future Directionmentioning
confidence: 99%
“…Adult patients with relapsed or refractory ALL have a poor prognosis and almost all patients will die from their disease [21][22][23][24][25][26][27][28]. While children are initially more responsive to traditional salvage chemotherapy approaches than adults, these remissions are often not sustained and relapsed ALL remains a leading cause of cancer deaths in children [29,30]. It is this dismal prognosis and lack of conventional treatment options, which underscores the impact of the dramatic responses observed with CD19-CAR T-cell therapy in patients with relapsed and refractory ALL [1,3,4,31,32].…”
Section: Clinical Outcomes Of Cd19-car T-cell Therapymentioning
confidence: 99%